Clinical relevance of double‐arm blood pressure measurement and prevalence of clinically important inter‐arm blood pressure differences in Indian primary care. Issue 8 (10th July 2022) - Wander, Gurpreet S.; McDonagh, Sinead T.J.; Rao, M. Srinivasa; Alagesan, R.; Mohan, J.C.; Bhagwat, Ajit; Pancholia, A.K.; Viswanathan, M.; Chopda, Manoj Bhavrilal; Purnanand, A.; kapardhi, P.L.N.; Vadavi, Arun R.; et al.
Abstract: Hypertension guidelines recommend measuring blood pressure (BP) in both arms at least once. However, this is seldom done due to uncertainties regarding measurement procedure and the implications of finding a clinically important inter‐arm BP difference (IAD). This study aimed to provide insight into the prevalence of clinically important IADs in a large Indian primary care cohort. A number of 134 678 (37% female) unselected Indian primary care participants, mean age 45.2 (SD 11.9) years, had BP measured in both arms using a standardized, triplicate, automated simultaneous measurement method (Microlife WatchBP Office Afib). On average, there were clinically minor differences in right and left arm BP values: systolic BP 134.4 vs 134.2 mmHg ( p  < .01) and diastolic BP 82.7 vs 82.6 mmHg ( p  < .01), respectively. Prevalence of significant mean systolic IAD between 10 and 15 mmHg was 7, 813 (5.8%). Systolic IAD ≥ 15 mmHg 2, 980 (2.2%) and diastolic IAD ≥ 10 mmHg 7, 151 (5.3%). In total, there were 7, 595 (5.6%) and 8, 548 (6.3%) participants with BP above the 140/90 mmHg threshold in only the left or right arm, respectively. Prevalence of participants with elevated BP on one arm only was highest in patients with a systolic IAD ≥ 15 mmHg; 19.1% and 13.7%, for left and right arm, respectively. This study shows that a substantial prevalence of IAD exists in Indian primary care patients. BP is above the diagnostic threshold for hypertension in one arm only for 6% of participants. These findings emphasize the importance of undertaking bilateral BP measurement in routine clinical practice.